Implementasi Media Pembelajaran Interaktif dalam Meningkatkan Hasil Belajar Mata Pelajaran Fiqih di MTs Al Huda 1 Karangpandan Tahun Ajaran 2025/2026 - Palupi, Wikan; Fathurrohman, Mukhlis (MAMBA'UL 'ULUM, 2026)
This study aims to describe the implementation of interactive learning media in improving students’ learning outcomes in Fiqh subjects at MTs Alhuda 1 Karangpandan in the 2025/2026 academic year and to identify the supporting and inhibiting factors in its implementation. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The research subjects consisted of the Fiqh teacher, seventh-grade students, and school staff involved in the learning process. The results show that the implementation of interactive learning media was carried out through planning, implementation, and evaluation stages. In the planning stage, the teacher prepared learning tools and selected media relevant to the Fiqh material. In the implementation stage, interactive media were used to present learning materials through images, videos, quizzes, and interactive exercises. In the evaluation stage, the teacher assessed students’ understanding through questioning, assignments, and classroom observation. The use of interactive learning media improved students’ motivation, participation, attention, and understanding of Fiqh materials. The supporting factors included teacher creativity, student enthusiasm, and school support, while the inhibiting factors included limited facilities, limited learning time, and unequal technological competence.